'Fragile States' in an Unequal World The Role of the g7+ in International Diplomacy and Development Cooperation - Rocha de Siqueira, Isabel (Open Book Publishers, 2022)
This is a book about people. 'Fragile States' in an Unequal World: The Role of the g7+ in International Diplomacy and Development Cooperation introduces the members of the g7+, a group formed by 20 conflict-affected states: why they came to believe in politics and policy; how they feel about their work, their family and their communities; and what they want to leave behind for the next generations. It is the story of their personal and collective values, their mistakes, and the challenges they faced, and it will resonate with anyone who has tried to organize and work with a group of very different people. This book is also a contribution for those seeking to influence international policy, especially from a disadvantageous position. It explores how to find your voice, use your survival skills, work with passion, decide how much to concede and act responsibly. Together, these lessons illuminate the paths that individual members have walked as they found their own voices, as well as how the g7+ fights to speak collectively. The book ends with a glimpse of the way forward, as Isabel Rocha de Siqueira encourages younger generations to engage with politics and policy generously, with hope for the future. Combining literature and hard facts - along with other elements such as illustrations, cartoon strips and photographs to tell the previously untold stories of public servants in poor, conflict-affected countries, the book offers an original (and very human) micro and macro perspective on the politics of development. It will be of interest to professionals in major development organisations, students and professors in development courses, policymakers, public servants, civil society, activists working for major international NGOs, and journalists who report on the development industry, as well as those with a general interest in international development cooperation, international diplomacy and other related fields.